Pengawasan Pendistribusian Bahan Bakar Minyak Bersubdi Kepada Nelayan Kecil Oleh Dinas Perikanan Kabupaten Merauke Berdasarkan Undang-Undang Nomor 7 Tahun 2016 - Handika Dwi Ardiansyah Pelu; Ricky Nelson Rumbewas (Universitas Musamus, 2024)
This research aims to find out how subsidized fuel oil is distributed to small fishermen by the Merauke Regency Fisheries Service based on Law Number 7 of 2016 concerning the Protection and Empowerment of Fishermen, Fish Farmers, and Salt Farmers and find out how Merauke District Fisheries Service monitors the distribution of subsidized fuel oil to small fishermen in Merauke district.This research is empirical juridical research. This research was conducted in the Merauke City Area at the Arafura Buti Street Oil Fuel Station and the Merauke Regency Fisheries Service.The research results in this thesis show that the Fisheries Service regulates the distribution of subsidized fuel oil by distributing fuel using a distribution strategy that is right on target by providing recommendations for purchasing subsidized fuel oil to fishermen. At the supervision stage, the government uses two instruments: control through recommendations given to small fishermen and supervision by assigning employees from the department to carry out supervision.